Problematika Penggunaan TPACK pada Pembelajaran IPS di SD Kelas Tinggi - Devyanne Oktari; Jessica Angeline De Eloisa Tobing; Tin Rustini (Departement of Mathematics Education, 2023)
The rapid advances in technology and information in various aspects of life, including education, have been mediated by the existence of technology, and the impact of these advances is that the requirements are more complex, challenging and there are specific specifications that are very influential to learning. This creates new problems in the teaching and learning processes. The purpose of this study is to find out what are the problems or obstacles in the use of TPACK in the learning of social studies in elementary school, especially in the upper grades. The data analysis techniques used technical methods of qualitative research. As a result of this study, it was found that there are problems that occur when using the TPACK method in middle school and elementary school social studies, including teachers who do not have a sufficient understanding of learning skills.